Recovery From Malnutrition Among Refugee Children Following Participation in the Special Supplemental Nutrition for Women, Infants, and Children (WIC) Program in Massachusetts, 1998-2010. Issue 1 (January 2020) - Smock, Laura; Martelon, MaryKate; Metallinos-Katsaras, Elizabeth; Nguyen, Thinh; Cochran, Jennifer; Geltman, Paul L.
Abstract : Objectives: (1) To examine patterns of catch-up growth and anemia correction in refugee children younger than 5 years after participation in the Special Supplemental Nutrition for Women, Infants, and Children (WIC) program, and (2) to identify factors associated with recovery from growth abnormalities. Design: Records on 1731 refugee children younger than 5 years who arrived in Massachusetts between 1998-2010 were matched to WIC program records and then restricted to 779 children who had at least 2 WIC visits. Kaplan-Meier curves and Cox proportional hazards models were used to examine how sex affected time to recovery from malnutrition and anemia. Factors associated with recovery were analyzed in SAS using multivariate logistic regression. Setting: Massachusetts. Participants: Refugee children younger than 5 years on arrival, who visited a WIC program at least twice between 1998 and 2010. Main Outcome Measures: (1) Proportion of children who recovered from low height-for-age (stunting), low weight-for-age, low weight-for-height (wasting), and anemia; (2) odds ratios for factors associated with recovery; and (3) Kaplan-Meier curves showing recovery over time from low height-for-age, low weight-for-age, and low weight-for-height. Results: The number of WIC visits was associated with recovery from stunting, wasting, low weight-for-age, and anemia; results reached statistical significance for stunting (odds ratio [OR] = 8.64; 95% confidence interval [CI], 2.25-33.19), low weight-for-age (OR = 5.28; 95% CI, 1.35-20.73), and anemia (OR = 6.50; 95% CI, 2.69-15.69). Female sex was associated with recovery from stunting, wasting, and low weight-for-age, whereas male sex was associated with recovery from anemia; the associations were statistically significant between female sex and stunting (OR = 9.14; 95% CI, 1.93-43.29), wasting (OR = 14.78; 95% CI, 1.57-138.85), and low weight-for-age (OR = 4.29; 95% CI, 1.09-16.79). Conclusions: Children who remained engaged in WIC may recover better from malnutrition than children with fewer WIC visits, although there are limitations to the available data. These findings suggest that those working with refugee families should prioritize outreach toward initiating and maintaining WIC program enrollment for eligible refugee children.